The development of welding fumes health risk assessment tool for automotive component related industries - Hariri, Azian (2015)
The environmental quality index had been applied and used widely for water and ambient air quality. However, indices for industrial indoor air pollutants are relatively novel and limited. Currently, the welding fume exposure risk assessments are largely focused on a single welding fume constituent approach because the regulatory standard for compliance only caters for a single constituent. However, in reality, welders are simultaneously exposed to multiple welding fume constituents at once. To fulfill this gap, welding fumes health index was developed by assigning doses rating and health risk rating to the multiple constituent of welding fumes and aggregated into index values. In the initial stage of this study, the type of health risks included in the index (sensitizer, respiratory toxins, target organ toxins, and carcinogenicity) and the related technical characteristics were determined by using quality function deployment approach. Personal samplings of welding fumes were conducted in Plant 1 and 2 to assess the concentration of metal constituents during the investigation of case studies along with a series of pulmonary function tests and questionnaire on persistent symptoms. Index values were derived from the aggregation analysis of metal constituent constituents while significant persistent symptoms and pulmonary functions were recognized through statistical analysis. The proposed index was then applied to a selected welding industry for verification purposes (Plant 3). The results of the study showed that the index value was directly proportional with the percentage decrease of the welder’s pulmonary functions in all investigated plants and the significant persistent symptoms (Plant 1: mean index value=1.42, FVC=84.09%, FEV1=88.51%, PEF= 68.58%, significant persistent symptom: sore or dry throat; Plant 2: mean index value=1.40, FVC=87.86%, FEV1=91.14%, PEF=71.68%, significant persistent symptom: none ;Plant 3: mean index value=1.30, FVC=89.65%, FEV1=91.96%, PEF= 80.57%, significant persistent symptom: none). The developed welding fumes health index showed its promising ability to rank welding workplace that associates well with persistent symptoms and pulmonary functions of the investigated welders.